2016
DOI: 10.1007/s13197-016-2369-7
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties and encapsulation of silicon in double emulsions for healthier food applications

Abstract: This article analyses the potential use of double emulsions as silicon delivery systems with reference to the influence of the composition of the inner aqueous phase (W, containing NaCl and sodium caseinate or gelatin) on silicon encapsulation and physicochemical properties of food-grade W/O/W. Irrespective of W, DEs initially showed a well-defined monomodal distribution, with the widest range registering in the sample with gelatin. All samples developed a bimodal distribution during storage (3 ± 2 °C). Heatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Lightness has been shown to decrease with storage time in all systems with the exception of GE-ISP-C which remained unchanged ( Table 2). The decrease of lightness normally occurred in simple emulsions, double emulsions and gelled double emulsion during their storage or as a consequence of other processing factors (Bou, Cofrades, & Jimenez-Colmenero, 2014a;Cofrades et al, 2016;Flaiz et al, 2016). Redness values were increased in GE-SC-C, GE-WPI-C, GE-WPI-Ex and GE-ISP-C with longer storage periods whereas the opposite trend was observed in GE-SC-Ex and GE-ISP-Ex.…”
Section: Effect Of Storage Timementioning
confidence: 98%
“…Lightness has been shown to decrease with storage time in all systems with the exception of GE-ISP-C which remained unchanged ( Table 2). The decrease of lightness normally occurred in simple emulsions, double emulsions and gelled double emulsion during their storage or as a consequence of other processing factors (Bou, Cofrades, & Jimenez-Colmenero, 2014a;Cofrades et al, 2016;Flaiz et al, 2016). Redness values were increased in GE-SC-C, GE-WPI-C, GE-WPI-Ex and GE-ISP-C with longer storage periods whereas the opposite trend was observed in GE-SC-Ex and GE-ISP-Ex.…”
Section: Effect Of Storage Timementioning
confidence: 98%
“…The rheology of ABIL EM 90 (also known by polyether-modified siloxane) stabilized internal dispersions in the fatty alcohol polyoxyethylene ether (AEO9)-containing outer water is unexplored, and the results showed promising stability for the future emulsions products . These dispersions prepared from ABIL EM 90 have been studied to exhibit excellent storage stability even under extreme cases (high temperatures and pressure) when compared to many other lipophilic emulsifiers. Of course, this type of stability dictates the strength of the emulsifying polymer that exhibits low impairment in viscoelastic behavior at the water/oil interface, in most cases, because of its chemical composition and structural presentation of the functional group. , ABIL EM 90 contains a repeating siloxane chain (Si–O) unit as a nonpolar group (wet in the oil phase) and a pendant polyether as a side chain that determines the water solubility and steric stabilization to the dispersed water droplets in the continuous oil phase . Such a chemical arrangement and structural presentation of ABIL EM 90 at the W/O interface quite pronounce the physical and chemical properties of the produced emulsions …”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that for a monodispersed W/O/W emulsion, a maximum close-packed structure was achieved at the dispersed phase ratio of 0.64. However, for polydisperse emulsions, the elastic jamming and maximum packing might be achieved at lower or higher dispersed phase ratios. , It was noticed that the viscoelastic region of randomly ordered emulsions observed with gel-like structures (repulsive gels) in which all movements of emulsions droplets were restricted. ,, Improvement in the thickening property of emulsions in one way or another has a direct correlation with storage stability, which accounts for a reduction in gravitational sedimentation (emulsion creaming) as a cost of increasing viscosity (because of the solid-like structure packing of oil globules in the external water phase). , It has been shown the rheological property of multiple emulsion determines qualities such as the processability, texture, mouthfeel, appearances, and their shelf life . In practical application, rheology defines the desired textural characteristics or control release phenomenal of multiple emulsion products of food, cosmetics, and pharmaceutical industries in terms of shear viscosity and elastic modulus (yield stress) as a function of shear forces (deformation).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por otra parte, el hipocampo, la amígdala y el tálamo han sido implicados junto con diversos núcleos del tronco del encéfalo (véase mas arriba) en la hiperalgesia térmica, mecánica, etc. inducidas en animales de experimentación por estresores como el frío, la inmovilización, la hipoglucemia, la natación forzada o la separación materna (98). tanto el eje HHA como el sistema nervioso simpático participan en la modulación del dolor por el estrés.…”
Section: Hiperalgesia Y Dolor Neuropáticounclassified